2012
DOI: 10.3168/jds.2011-4804
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction for Nordic Red Cattle using one-step and selection index blending

Abstract: This study investigated the accuracy of direct genomic breeding values (DGV) using a genomic BLUP model, genomic enhanced breeding values (GEBV) using a one-step blending approach, and GEBV using a selection index blending approach for 15 traits of Nordic Red Cattle. The data comprised 6,631 bulls of which 4,408 bulls were genotyped using Illumina Bovine SNP50 BeadChip (Illumina, San Diego, CA). To validate reliability of genomic predictions, about 20% of the youngest genotyped bulls were taken as test data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 35 publications
(62 reference statements)
11
119
7
2
Order By: Relevance
“…On the other hand, the multi-step method has the flexibility to use prediction methods such as Bayesian methods and could easily use EBV from multi-trait acrosscountry evaluation in the reference population including genotyped foreign bulls. Some studies have compared the single-step and multi-step methods (Su et al, 2012;Lourenco et al, 2014). However, few studies have compared the results obtained with and without genotyped cows analyzed by both single-step and multi-step methods.…”
Section: Prediction Methodsmentioning
confidence: 99%
“…On the other hand, the multi-step method has the flexibility to use prediction methods such as Bayesian methods and could easily use EBV from multi-trait acrosscountry evaluation in the reference population including genotyped foreign bulls. Some studies have compared the single-step and multi-step methods (Su et al, 2012;Lourenco et al, 2014). However, few studies have compared the results obtained with and without genotyped cows analyzed by both single-step and multi-step methods.…”
Section: Prediction Methodsmentioning
confidence: 99%
“…In this study, ω = 0.20 was chosen according to the previous studies in Improving genomic predictions in Danish Jersey Nordic cattle populations 2012c;Gao et al, 2012). In this setting, the GBLUP model is equivalent to a GBLUP including a genomic effect and a residual polygenic effect accounting for 80% and 20% of total additive genetic variance, respectively.…”
Section: Datamentioning
confidence: 99%
“…Until now, only about 1200 to 1400 Danish progeny-tested bulls (depending on trait) are available to be used as reference bulls. Due to the small reference population, accuracy of genomic prediction in the Danish Jersey is much lower than in the Danish Holstein and Red Cattle populations 2012c;Gao et al, 2012;Thomasen et al, 2012). Therefore, it is important to find efficient approaches to improve accuracy of genomic prediction in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Several results have been reported around the world. Several authors reported that the reliabilities of genomic estimated breeding values (GEBV) were substantially greater than breeding values from estimated breeding values (EBV) based on pedigree information [29]. The accuracy of selection was different between countries [12].…”
Section: Applications In Genomicsmentioning
confidence: 99%
“…The accuracy of selection was different between countries [12]. The accuracy was dependent on the size of reference population, the heritability of the trait studied, the statistical models and approaches used for prediction of genetic values for quantitative traits, and the method achieved to estimate the accuracy [12,27,29]. Ref.…”
Section: Applications In Genomicsmentioning
confidence: 99%